A simple angiographic index to predict adverse clinical outcome associated with acute myocardial infarction - Mustafa Tarık Ağaç; Süret Ağaç; Levent Korkmaz; Hakan Erkan; Turhan Turan; Hüseyin Bektaş; Ali Rıza Akyüz; Mustafa Çetin; Şükrü Çelik (KARE Publishing, 2014)
Objectives: The major determinant of final infarct size for a given coronary occlusion is the size of the myocardial areaat- risk. We propose herein a new index 'Relative Importance Index (RII)' to predict area-at-risk in patients with anterior myocardial infarction (MI). The aim of the study was to assess the predictive value of RII in left ventricle (LV) systolic function reduction and its relation to adverse clinical outcome. Study design: One hundred twenty-three acute anterior MI patients with their first acute coronary syndrome incident were consecutively and prospectively enrolled in to the study. RII was calculated by dividing the culprit segment diameter by the sum of diameters of the left anterior descending, circumflex, and right coronary arteries at their proximal segments. We evaluated the one-month follow-up rates of major clinical endpoints, which were defined as death, non-fatal MI, stroke, and new congestive heart failure (CHF). Results: RII was significantly and negatively correlated with left ventricular ejection fraction (LVEF) (r=-0.65, p<0.001). Likewise, RII was significantly correlated with 72 hour troponin I (TnI) (r=0.48, p<0.001). Patients were dichotomized according to the median value of RII (median RII: 0.30). Supra-median RII was associated with lower EF (32.8+-8.6 vs. 42.8+-9.4, p<0.001) and higher incidence of composite major adverse cardiac events (33.9% vs. 13.1%, p=0.01). The mortality, non-fatal MI and new CHF rates in the supra-median RII group trended higher but they did not reach statistical significance. An RII >0.30 had an 88% sensitivity and 60% specificity (ROC area: 0.82, p<0.001, CI: 0.73-0.90) for predicting severe LV dysfunction (LVEF <30%). Conclusion: A simple index derived from coronary angiography at the time of primary percutaneous coronary intervention can predict LV systolic function loss and adverse clinical outcome in patients with acute anterior MI.